THE ROLE OF BANKS IN SUPPORTING ENTREPRENEURSHIP AND INNOVATION - Neharika; Yadav, Sanjay Kumar; Kadakia, Babita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines how banks may support innovation and entrepreneurship, with special focus on the problem of access to loans by entrepreneurs and the criteria used by banks. The research approach adopted was descriptive with the use of purposive sampling that ensured relevant participation. In all, 180 entrepreneurs in the Mysore region were included in the sample. Standardized questionnaires and in-person interviews were used to collect information on services provided by banks, loan approval procedures, the problems owners face, and requirements for lending. While there are positive outcomes among business owners who are able to acquire loans, interest rates, poor credit history, and collateral requirements are some of the problems that are common nowadays. Furthermore, it does nothing for banks to make market access easy and promote innovation funding. The research also identifies lending decision factors with loan terms, financial capability, and collateral as some of the key variables. In light of the findings the research recommends improved flexibility of loan terms, greater entrepreneurial development support, and enhanced financial literacy in creating an atmosphere that is more conducive to innovation and expansion.